Serratiopeptidase Niosomal Gel with Potential in Topical Delivery. (20th March 2014) - Shinde, Ujwala A.; Kanojiya, Shivkumar S.
Abstract : The objective of present study was to develop nonionic surfactant vesicles of proteolytic enzyme serratiopeptidase (SRP) by adapting reverse phase evaporation (REV) technique and to evaluate the viability of SRP niosomal gel in treating the topical inflammation. The feasibility of SRP niosomes by REV method using Span 40 and cholesterol has been successfully demonstrated in this investigation. The entrapment efficiency was found to be influenced by the molar ratio of Span 40 : cholesterol and concentration of SRP in noisome. The developed niosomes were characterized for morphology, particle size, and in vitro release. Niosomal gel was prepared by dispersing xanthan gum into optimized batch of SRP niosomes. Ex vivo permeation and in vivo anti-inflammatory efficacy of gel formulation were evaluated topically. SRP niosomes obtained were round in nanosize range. At Span 40 : cholesterol molar ratio 1 : 1 entrapment efficiency was maximum, that is, 54.82% ± 2.08, and showed consistent release pattern. Furthermore ex vivo skin permeation revealed that there was fourfold increase in a steady state flux when SRP was formulated in niosomes and a significant increase in the permeation of SRP, from SRP niosomal gel containing permeation enhancer. In vivo efficacy studies indicated that SRP niosomal gel had a comparable topical anti-inflammatory activity to that of dicolfenac gel.